2002
DOI: 10.20870/productions-animales.2002.15.5.3711
|View full text |Cite
|
Sign up to set email alerts
|

La biologie de la truite commune (Salmo trutta L.) dans la rivière Scorff, Bretagne : une synthèse des études de 1972 à 1997

Abstract: Cet article synthétise l’ensemble des études menées sur la biologie et l’écologie de la truite commune (Salmo trutta L.) sur le bassin du Scorff (Morbihan, Bretagne) de 1972 à 1997. Après une brève présentation de la taxonomie et des caractéristiques écologiques générales de l’espèce, les principaux résultats obtenus sont abordés en termes d’éléments de description et de dynamique de populations. La répartition et l’abondance de la truite sur le bassin varient en fonction de l’âge, du milieu (affluent, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…S YOY =0.51 and S juveniles =0.50 were derived from Elliott and Hurley (1998) (assuming a constant mortality rate across time). These rates were consistent with values observed in other brown trout populations (Needham et al 1945, McFadden and Cooper 1962, Hunt 1969, Mortensen 1977, Brynildson and Brynildson 1984, Olsen and Vollestad 2001, Baglinière and Maisse 2002). S adults was fixed at 0.50 (Needham et al 1945, McFadden and Cooper 1962, Hunt 1969, Baglinière and Maisse 2002).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…S YOY =0.51 and S juveniles =0.50 were derived from Elliott and Hurley (1998) (assuming a constant mortality rate across time). These rates were consistent with values observed in other brown trout populations (Needham et al 1945, McFadden and Cooper 1962, Hunt 1969, Mortensen 1977, Brynildson and Brynildson 1984, Olsen and Vollestad 2001, Baglinière and Maisse 2002). S adults was fixed at 0.50 (Needham et al 1945, McFadden and Cooper 1962, Hunt 1969, Baglinière and Maisse 2002).…”
Section: Methodssupporting
confidence: 91%
“…The studies conducted by Elliott and Hurley (1998) and Lobón‐Cervià (2003) indicated that variability in adult survival was low. Moreover, mean survival after the first year is generally high, ranging from 27% to 55% (Needham et al 1945, McFadden and Cooper 1962, Hunt 1969, Mortensen 1977, Elliott and Hurley 1998, Olsen and Vollestad 2001, Baglinière and Maisse 2002). The lowest estimates are probably underestimated because of technical difficulties (catchability, tag loss, migration) or interspecific competition (Olsen and Vollestad 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Ire, Gotland, brown trout ascending to spawn entered the rivers only a short time before spawning took place and most of the fish descended to the sea as soon as the spawning was over (Hessle, 1935), just as in Själsöån. Migration in Själsöån depends much on hydraulic conditions, such as an increase in water discharge, as observed elsewhere (Alm, 1950; Campbell, 1977; Elliott, 1987; Berg & Berg, 1989; Baglinière & Maisse, 2002). In the River Tweed, Scotland, the fish which had spent the longest period of time upstream were in the poorest condition (Campbell, 1977), just as in Själsöån.…”
Section: Discussionmentioning
confidence: 54%
“…Male and female brown trout Salmo trutta L. show alternative reproduction tactics (Campbell, 1977; Dellefors & Faremo, 1988; Berg & Berg, 1989; Garcia‐Vazquez et al ., 2001; Jonsson et al ., 2001). Moreover, some individuals are fully stream resident whereas some migrate from lake to stream, or from sea to stream (Campbell, 1977; Jonsson, 1985, 1989; Berg & Berg, 1989; Jonsson & Jonsson, 1993; Jonsson et al ., 2001; Baglinière & Maisse, 2002; Klemetsen et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%